Preliminary in vitro hemolysis evaluation of MR-conditional blood pumps - Schulte, Dominik T.; Pietsch, Carolina; Topalovic, Natalija; Hofmann, Michael; Schmiady, Martin O.; Weisskopf, Miriam; Schmid Daners, Marianne (Frontiers in Medical Technology, 2025)
PurposeMagnetic resonance imaging (MRI) during cardiopulmonary bypass is hindered by the incompatibility of conventional heart-lung machines, which contain metallic components that interfere with the MRI environment. This study evaluates the hemolytic performance of three MR-conditional blood pump prototypes—roller, non-occlusive roller, and centrifugal—designed for use during neonatal surgery.Materials and methodsEach pump was tested using acid-citrate dextrose-stabilized bovine blood at a neonatal-relevant flow rate of 1 L/min. Due to limitations of the setup, a low pressure head of 10 mmHg was applied uniformly across experiments. Hemolysis was assessed using normalized index of hemolysis, and a linear mixed-effects model was applied to account for experimental variability.ResultsThe roller pump showed the lowest hemolysis (1.84 ± 1.90 mg/100 L). The centrifugal pump showed the highest (8.43 ± 1.63 mg/100 L), alongside mechanical leakage. Random effects (SD = 2.07) indicated moderate inter-experimental variability.ConclusionWhile all prototypes performed comparably to standard references under controlled conditions, further testing at physiological pressure levels and stricter adherence to ASTM F1841 is necessary for broader validation.